AGRESI RUSIA TERHADAP UKRAINA DIKECAM SEBAGAI PELANGGARAN BERAT HAK ASASI MANUSIA - Rohmah, Siti; Wahyudi, Wahyudi; Sita, Nur (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
This legal inquiry discusses the serious human rights violations resulting from the Russian invasion. To Ukraine. This study refers to the Universal Declaration of Human Rights and its legal provisions. international. Russia bombs and bombards the settlements, resulting in deaths They attack not only civilians but also various civilian infrastructure such as hospitals and schools. It is a fundamental violation of various regulations and laws. international. The purpose of this investigation is to determine the invasion action of Russia. Forms of responsibility and sanctions for human rights violations in Ukraine and Russia Human rights were violated during the invasion of Ukraine. method In this study, by analyzing the data using legal normative methods, Additional libraries or data. This investigation is the result of monitoring violations. The UN and ground forces opposed Russia's invasion of Ukraine, and Russia was condemned. An immediate and complete cessation of hostilities against Ukraine. This is the location of the business Limits of international law, compliance by countries in conflict Norms and standards of international law. Russia must participate in this conflict Knowing and following the rules and regulations of international law is the only way here. Peacefully resolve the conflict between Russia and Ukraine